HLA class II-restricted T cell epitopes in public neoantigens of ESR1 and PIK3CA in breast cancer - Yukari Ando; Hiroko Miyadera; Hiroko Bando; Sachie Hashimoto; Emiko Noguchi; Hisato Hara (BMC Cancer)
Abstract Background The high occurrence of treatment resistance in patients with hormone receptor-positive (HR +) breast cancer is a global health concern. Thus, effective immunotherapy must be developed. The public neoantigens, estrogen receptor 1 (ESR1) and phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA), shared by HR + and endocrine-resistant breast cancer, could be ideal targets for immunotherapy; however, their presentation by human leukocyte antigen class II (HLA II) and recognition by CD4 + T cells remain largely unknown. Methods Seven mutations in ESR1 and ten mutations in PIK3CA were subjected to major histocompatibility complex (MHC)-peptide binding analysis and enzyme-linked immunospot (ELISPOT) assays using peripheral blood mononuclear cells (PBMCs) from healthy donors carrying DRB4*01:03, or DRB4*01:03 and DPA1*02:02-DPB1*05:01 (DP5). DRB4*01:03- or DP5-restricted peptides were inferred from binding measurements and ELISPOT assays. Other DRB1 alleles that can also present these mutant peptides were identified using binding measurements. Results Positive IFN-γ responses by CD4 + T cells were detected for most peptides. The peptides that contain ESR1 (E380Q) and PIK3CA (N345K, E542K, E545K/A, E726K, H1047R/L/Y, and G1049R) are presumably restricted by DRB4*01:03, which is frequently found globally (carrier frequency: 35–63%), or by DRB4*01:03 and DRB1*04 alleles. Some PIK3CA (H1047R/L/Y) peptides can also be presented by DRB1*01:01, DRB1*09:01, DRB1*11:01, and DRB1*15:02. ESR1 (Y537S/N, D538G) peptides are potentially restricted by DP5, a frequently found allele in East Asian populations, and DRB1*01:01 and DRB1*15:01. Conclusions Mutations in ESR1 and PIK3CA were recognized by CD4 + T cells from healthy donors through potential restriction by common HLA II alleles. Further studies are warranted to elucidate the landscape of HLA II presentation and validate the clinical applicability of these mutations for the immunotherapy of patients with endocrine-resistant breast cancer.